The influence of β-carotene on homocysteine level and oxidative stress in lead-exposed workers - Sławomir Kasperczyk; Michał Dobrakowski; Janusz Kasperczyk; Ewa Romuk; Adam Prokopowicz; Ewa Birkner (Nofer Institute of Occupational Medicine, 2014)
Background: Oxidative stress is involved in lead toxicity. This suggests that some antioxidants may play a role in the treatment of lead poisoning. In the light of this, the aim of the study was to determine whether β-carotene administration reduces oxidative stress and homocysteine level in workers chronically exposed to lead. Material and Methods: The exposed population included healthy male workers exposed to lead who were randomly divided into 2 groups (mean blood lead level ca. 44 μg/dl). Workers in the 1st group (N = 49, reference group) had no antioxidants, drugs, vitamins or dietary supplements administered, while workers in the 2nd group (N = 33) had β-carotene administered in a dose of 10 mg per day for 12 weeks. Biochemical analysis included markers of lead-exposure and the level of malondialdehyde (MDA), an oxidative stress biomarker. We also measured the level of homocysteine (Hcy) and thiol groups as well as the activity of superoxide dismutase (SOD) and its isoenzyme EC-SOD in serum. Results: After supplementation, the level of MDA significantly decreased, compared to baseline, by 16%, and to the reference group. When compared to the reference group, Hcy level was also significantly decreased. However, the level of thiol groups was significantly higher after supplementation with β-carotene compared to the reference group. Analogically, the activity of SOD and EC-SOD was significantly higher compared to the baseline and to the reference group. Conclusions: Despite some controversies over antioxidant properties of β-carotene, our results indicate that its antioxidant action could provide some beneficial effects in lead poisoning independent of chelation. Med Pr 2014;65(3):309-316